Gossypium ekmanianum (malvaceae), algodón silvestre de la República Dominicana - Krapovickas, Antonio; Seijo, José Guillermo (Instituto de Botánica del Nordeste, 2008)
Se confirma la observación de Ekman sobre la condición de silvestre de Gossypium Ekmanianum y se corrige su país de origen.

The remark «perfectly wild» made by Ekman for Gossypium Ekmanianum is confirmed and its country of origin is corrected.
Gossypium Ekmanianum (Malvaceae), a wild cotton from Dominican Republic
Keywords: Algodón; Silvestre; Malvaceae; Cotton; Wild; Malvaceae